1, 1, 2-Tribromoethyl arenes: novel and highly efficient precursors for the synthesis of 1-bromoalkynes and α-bromoketones. Issue 16 (16th July 2021) - Lin, Xia; Fang, Chengtao; Huang, Xiaolei; Xiao, Xiaohui
Abstract : A novel tribromination method to prepare versatile intermediate 1, 1, 2-tribromoethyl arenes, which can not only be transformed to synthetically valuable 1-bromoalkynes via elimination but also be hydrolyzed to a variety of α-bromoketones, was developed. Abstract : In this work, we developed a novel method to synthesize 1, 1, 2-tribromoethyl arenes, which can be easily transformed to 1-bromoalkynes via base-mediated elimination reaction. The bromination reagent was in situ generated from the reaction of NaBr/NaBrO3 /H2 SO4, resulting in high reactivity, excellent chemical selectivity and outstanding functional group tolerance. Moreover, 1, 1, 2-tribromoethyl arenes encounter a selectivity switch to afford α-bromoketones under strong acidic conditions.